Understanding the Provisions for Local Government Planning in Nepal - Adhikari , Govinda (Intellectual Journal of Academic Research, 2024)
This study examines the provisions for local government planning in federal Nepal, focusing on annual planning processes. The primary objective is to analyze the existing framework and guidelines, including the Constitution of Nepal (2015), the Local Government Operation Act (LGOA, 2017), and the Inter-governmental Fiscal Management Act (IGFMA, 2017). The analysis centers on the provisions related to Annual Plans, structures, and processes. Employing a qualitative approach, the study utilizes document and literature reviews to explore these provisions without delving into practical implementation. Key findings reveal that the legal framework mandates a structured approach to planning, including criteria for project prioritization, sectoral coverage, and a participatory planning process. The study highlights the role of key committees and the Seven-Step Planning Process in ensuring comprehensive and inclusive planning. Recommendations include strengthening training programs, enhancing transparency measures, and encouraging innovative solutions to improve the effectiveness of annual planning provisions.